2020
DOI: 10.1021/acsami.0c07917
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Single-Particle Tracking and Dynamic pH Sensing Reveal Lysosome-Targetable Mesoporous Silica Nanoparticle Pathways

Abstract: Nanoparticle (NP)-based targeted drug delivery is intended to transport therapeutically active molecules to specific cells and particular intracellular compartments. However, there is limited knowledge regarding the complete route of NPs in this targeting scenario. In this study, simultaneously performing motion and dynamic pH sensing using single-particle tracking (SPT) leads to an alternative method of gaining insights into the mesoporous silica nanoparticle's (MSN) journey in targeting lysosome. Two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…To improve our understanding of the influence of NP physicochemistry in passive diffusion to their accumulation in spheroids, we further adopted the zombie cell method developed by Warren et al [ 35 , 36 ]. Spheroids were fixed overnight under 4% PFA to ensure that all the cellular dynamics and cellular uptake processes were halted, allowing only NP diffusion to dominate the penetration process.…”
Section: Resultsmentioning
confidence: 99%
“…To improve our understanding of the influence of NP physicochemistry in passive diffusion to their accumulation in spheroids, we further adopted the zombie cell method developed by Warren et al [ 35 , 36 ]. Spheroids were fixed overnight under 4% PFA to ensure that all the cellular dynamics and cellular uptake processes were halted, allowing only NP diffusion to dominate the penetration process.…”
Section: Resultsmentioning
confidence: 99%
“…>5000) within the matrix of mesoporous silica nanoparticle (MSNs) [ 44 ] and the compartmentations by the pores of MSNs prevented aggregation‐induced self‐quenching and photobleaching of the encapsulated dyes and minimize sensing interference from cell components. [ 34 ] These overall excellent properties made them suitable probes for long‐term monitoring of dynamic pH values throughout the phagocytosis using single‐particle tracking.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of FRMSNs was based on a Stöber-like process developed by Mou and co-workers. [33,34] To generate wide-range ratiometric pH sensing which covers pH values of phagocytosis, double pH sensitive dyes FITC (pK a = 6.7) and OG (pK a = 4.1), and one reference RITC were cocondensed with a silica precursor to form triple dye-labeled MSNs. The chemical structure of the FRMSN +/− (FRMSN + or FRMSN − ) synthesized in this study is demonstrated in Figure 1B.…”
Section: Synthesis and Characterization Of Pu Frmsn − Frmsn + Frmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). More details can be found in the Supplementary Material and a recent publication (Chang et al, 2020). In that design, the authors successfully tracked the constant spatial movement and morphological changes of a single fluorescent nanoparticle inside a cell.…”
Section: Introductionmentioning
confidence: 99%